2015
DOI: 10.1093/jxb/eru490
|View full text |Cite
|
Sign up to set email alerts
|

Plant defence responses in oilseed rape MINELESS plants after attack by the cabbage moth Mamestra brassicae

Abstract: HighlightThe larvae of Mamestra brassicae feed less and show reduced growth on plants with ablated myrosin cells, which raises questions about the role of defence cells in Brassicaceae plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…In our previous studies with Brassica napus transgenic MINELESS plants, which are deficient in myrosinase activity, we showed that MINELESS seedlings accumulated higher levels of glucosinolates14. Likewise, in the present study, the levels of certain glucosinolates were observed to be different in leaves of WT and tgg single and double mutants (Figs 6 and 7).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In our previous studies with Brassica napus transgenic MINELESS plants, which are deficient in myrosinase activity, we showed that MINELESS seedlings accumulated higher levels of glucosinolates14. Likewise, in the present study, the levels of certain glucosinolates were observed to be different in leaves of WT and tgg single and double mutants (Figs 6 and 7).…”
Section: Discussionsupporting
confidence: 76%
“…This is in terms of their interactive effect relating to insect herbivores by extracting glucosinolates from the leaf surface91011, or glucosinolates possibly originating from deeper leaf layers, herbivores penetrating the wax layer and perceiving compounds like isothiocyanates in deeper layers or through stomata12. Glucosinolates are structurally diverse phytochemicals produced throughout the Brassicaceae, including Arabidopsis thaliana and Brassica crop species81314. They comprise one component of the dual glucosinolate-myrosinase system, in which myrosinase thioglucosidase (TGG) (EC 3.2.3.147) catalyses glucosinolate breakdown into various biologically active molecules upon tissue disruption or insect attack141516.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Atle Bone’s laboratory has previously used a novel technique to produce oilseed rape plants that lack myrosinase-containing myrosin cells, which are normally distributed throughout plant tissues ( Ahuja et al , 2011 ). In this volume, the paper by Ahuja et al (2015) describes a series of experiments in which MINELESS plants were used to dissect the role of glucosinolate breakdown products in plant resistance to the cabbage moth Mamestra brassicae . MINELESS plants exhibited negligible levels of myrosinase activity and had higher total glucosinolate concentrations in both the absence and the presence of M. brassicae larvae with altered abundance of individual glucosinolates.…”
mentioning
confidence: 99%
“…The major defense in Brassicaceae family was the glucosinolate–myrosinase system. When insect herbivores attack plant tissues, glucosinolates are hydrolyzed by the enzyme myrosinase into a variety of toxic products, which can deter further herbivory (Ahuja et al., ). Cassia obtusifolia (Caesalpinioideae, Leguminosae) is a nonhost plant of P. rapae , and an important herb commonly found in subtropical areas.…”
Section: Introductionmentioning
confidence: 99%